PENGARUH PENGERJAAN DINGIN (COLD WORKING) PADA BAJA TAHAN KARAT JENIS AUSTENITIK (AUSTENITIC STAINLESS STEEL) TYPE 304 - Agus Setiyo Umartono (Wahana Teknik, 2012)
Stainless steel (Stainless Steel) is actually an alloy of steel alloy with high levels (High alloy steel), stainless steels have properties that privileges resistant to corrosion and high temperatures. Corrosion resistant properties obtained from the oxide layer (especially chrome) which are very stable on the surface of the steel and protects the steel against the corrosive environment.Stainless steel (Stainless Steel), the most popular and widely used is the type Austenitic stainless steels, because it has high shock resistant properties, tenacious, are not interested in magnetic, corrosion resistant and has the most good weldability (weldability) is good.However, austenitic stainless steels (austenitic stainless steel) type 304 is very difficult to do Cold Work. Because of cold work on type 304 austenitic stainless steel can provide a change of mechanical properties vary greatly.For that reason in this thesis will be carried out cold work. (cold work) by Rolling / Bending of material type austenitic stainless steel 304. The changes observed. In the event of changes in the nature kemagnetannya Cosmos, the second material is different is, each testing the mechanical properties (Pull, Violence, Chemical Composition, Structure and Corrosion Micro).From the test results are then compared and conducted studies of crystal structure, as additional data to draw conclusions.Keywords : Austenitic Stainless Steel , Cold Work, changes